Актуальні проблеми інформаційної безпеки в телекомунікаційній галузі - Куля, Ю. Е. (ХНУРЕ, 2023)
The purpose of this paper is to provide advice on current risks and highlight potential future threats affecting the telecommunications industry, and to explain how ISPs can use Threat Intelligence to help protect their digital environment and critical infrastructure from emerging cyber threats.
Keywords: проблеми інформаційної безпеки; кібербезпека